A chromosome‐scale assembly of allotetraploid Brassica juncea (AABB) elucidates comparative architecture of the A and B genomes. Issue 3 (30th December 2020) - Paritosh, Kumar; Yadava, Satish Kumar; Singh, Priyansha; Bhayana, Latika; Mukhopadhyay, Arundhati; Gupta, Vibha; Bisht, Naveen Chandra; Zhang, Jianwei; Kudrna, David A.; Copetti, Dario; Wing, Rod A.; Reddy Lachagari, Vijaya Bhasker; et al.
Summary: Brassica juncea (AABB), commonly referred to as mustard, is a natural allopolyploid of two diploid species— B. rapa (AA) and B. nigra (BB). We report a highly contiguous genome assembly of an oleiferous type of B. juncea variety Varuna, an archetypical Indian gene pool line of mustard, with ~100× PacBio single‐molecule real‐time (SMRT) long reads providing contigs with an N50 value of >5 Mb. Contigs were corrected for the misassemblies and scaffolded with BioNano optical mapping. We also assembled a draft genome of B. nigra (BB) variety Sangam using Illumina short‐read sequencing and Oxford Nanopore long reads and used it to validate the assembly of the B genome of B. juncea . Two different linkage maps of B. juncea, containing a large number of genotyping‐by‐sequencing markers, were developed and used to anchor scaffolds/contigs to the 18 linkage groups of the species. The resulting chromosome‐scale assembly of B. juncea Varuna is a significant improvement over the previous draft assembly of B. juncea Tumida, a vegetable type of mustard. The assembled genome was characterized for transposons, centromeric repeats, gene content and gene block associations. In comparison to the A genome, the B genome contains a significantly higher content of LTR/Gypsy retrotransposons, distinct centromeric repeats and a large number of B. nigra specific gene clusters that break the gene collinearity between the A and the B genomes. The B. juncea Varuna assembly will be of major value to the breeding work on oleiferous types of mustard that are grown extensively in south Asia and elsewhere.